DETERMINATION OF DEPENDENCE OF CHEWELESS EFFECTS FROM TEMPERAMENT - K.D. Toncheva; D.M. Korol; I.V. Zaporozhchenko; D.V. Kalashnikov; D.D. Kindii (Український стоматологічний альманах)
Introduction. Studies have shown that the style of each person's activity largely depends on the type of higher nervous activity entering the structure of his temperament.